2017
DOI: 10.1177/0036933017727969
|View full text |Cite
|
Sign up to set email alerts
|

Delays in diagnosis are associated with poorer outcomes in adult hip dysplasia

Abstract: Background and Aims Developmental dysplasia of the hip is a common cause of osteoarthritis. Periacetabular osteotomy can restore femoral head coverage; however, it is reserved for patients with minimal articular degeneration. We examined the relationship between delays in diagnosis and outcomes. Methods We identified patients presenting to a hip specialist with a new diagnosis of hip dysplasia. The time taken between patients presenting to their general practitioner and attending the young adult hip clinic was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“… 17 Our findings align with existing knowledge that later diagnosis may require more invasive treatments. 4 6 Participant-reported age at first surgery suggests a lapse between diagnosis and surgery where other treatment options were employed. 17 …”
Section: Discussionmentioning
confidence: 99%
“… 17 Our findings align with existing knowledge that later diagnosis may require more invasive treatments. 4 6 Participant-reported age at first surgery suggests a lapse between diagnosis and surgery where other treatment options were employed. 17 …”
Section: Discussionmentioning
confidence: 99%
“…(iv, v) Hip osteoarthritis and hip replacement study: Studies demonstrated that even after undergoing osteotomy surgeries, there is still a percentage of patients who progress to osteoarthritis and require arthroplasty ( 47 ). If left untreated, patients with early-stage DDH definitively develop secondary osteoarthritis, with 50% of these patients developing advanced osteoarthritis at the age of 50 years ( 48 ). Developmental dysplasia of the hip was recognized as a significant risk factor in hip osteoarthritis in adults.…”
Section: Discussionmentioning
confidence: 99%
“…Kennedy et al . [ 5 ] from Glasgow, UK examined the relationship between delay and diagnosis and outcomes of dysplasia surgery. They identified patients presenting to a hip specialist with a new diagnosis of hip dysplasia.…”
Section: Are Delays In Diagnosis Associated With Poorer Outcomes In Amentioning
confidence: 99%